The impact of Cesarean section on female fertility: a narrative review - Lorenz Hinterleitner; Herbert Kiss; Johannes Ott (IMR Press, 2021)
Objective: The mode of giving birth has changed over the years. In 1990, approximately 10% of women delivered by Cesarean section (CS), whereas this procedure is performed daily in obstetrics today. When a surgical intervention performed, it is necessary to consider special risks and complications, including long-term effects. Mechanism: This review focuses on fertility after CS. Evidence suggests that many women who aim to have subsequent children have difficulties becoming pregnant after they have delivered by CS. Findings: There are several causes for subfertility/infertility after CS, including post-Cesarean niches, intraabdominal adhesions, and the preference for a smaller family size, among others. Conclusion: This review provides an overview of the available literature, which supports the conclusion that CS is associated with decreased odds of subsequent pregnancy and live birth.